RHEUMATOID ARTHRITIS (RA) AND ITS IMPACT ON KIDNEYS - Sayfutdinova Z. A; Meliboyeva X. S (Scholar Express Journals, 2025)
Rheumatoid arthritis (RA) is one of the most common autoimmune diseases globally, significantly affecting patients' quality of life. This chronic inflammatory condition primarily affects the joints but can also impact internal organs, including the kidneys. The aim of this article is to analyze the impact of rheumatoid arthritis on kidney function, explore the mechanisms of disease development, diagnostic methods, complications, and treatment strategies. The article discusses the effect of RA on the kidneys, including complications such as amyloidosis, and the side effects of medications used to control inflammation that can affect kidney function. The importance of early diagnosis and timely treatment, as well as the need for regular monitoring of kidney health, is emphasized. Diagnostic methods such as microalbuminuria and treatment approaches aimed at preserving kidney function are also reviewed. In conclusion, effective management of RA requires a comprehensive approach, involving medication, rehabilitation, and psychological support for patients.
Keywords: rheumatoid arthritis; kidney failure; amyloidosis